2004
DOI: 10.1177/108705470400700402
|View full text |Cite
|
Sign up to set email alerts
|

Reactive vs. proactive antisocial behavior: Differential correlates of child ADHD symptoms?

Abstract: This study examines the relation between proactive and reactive antisocial behavior with Attention-Deficit/Hyperactivity Disorder (ADHD) symptoms. Caregivers of children aged 8 to 15 (n = 84) being evaluated at a child psychiatry outpatient clinic served as participants. Given the conceptual similarity between reactive antisocial behavior (ASB) and particular ADHD symptoms, we hypothesized that ADHD symptoms would be more closely related to reactive than to proactive ASB. Based on peer deviancy training models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 49 publications
3
31
0
Order By: Relevance
“…ADHD symptoms that may be implicated in becoming a bully include especially impulsive behavior, lack of control, reduced empathy and aggressive reactions, often owing to the frustrations experienced at school. These findings are consistent with a large number of studies that have pointed to an association between ADHD and aggressive behavior [Bennett et al, 2004;Dodge et al, 1997;Kitchens et al, 1999] that, in turn, is strongly associated with rejection by the peer group [Bierman et al, 1993;Coie et al, 1992;Rubin et al, 2006]. It seems likely that these effects give rise to a vicious circle.…”
Section: Discussionsupporting
confidence: 89%
“…ADHD symptoms that may be implicated in becoming a bully include especially impulsive behavior, lack of control, reduced empathy and aggressive reactions, often owing to the frustrations experienced at school. These findings are consistent with a large number of studies that have pointed to an association between ADHD and aggressive behavior [Bennett et al, 2004;Dodge et al, 1997;Kitchens et al, 1999] that, in turn, is strongly associated with rejection by the peer group [Bierman et al, 1993;Coie et al, 1992;Rubin et al, 2006]. It seems likely that these effects give rise to a vicious circle.…”
Section: Discussionsupporting
confidence: 89%
“…These results resemble findings from studies with ADHD children and adolescents, which have reported a closer relation of ADHD with reactive aggression than with proactive aggression (Bennett et al 2004;Waschbusch and Willoughby 2007). Likewise, Dowson and Blackwell (2010) recently reported findings from a study with adults with ADHD, which indicate that ADHD is a predictor for comorbid impulsive aggression.…”
Section: Modelsupporting
confidence: 83%
“…Accordingly, it has been demonstrated in children with conduct problems that ADHD is a moderator of reactive but not proactive aggression (Waschbusch and Willoughby 2007). In addition, Bennett et al (2004) showed that reactive antisocial behavior was more closely related to ADHD than proactive antisocial behavior in 8-15 year old children and that the relation between ADHD symptoms and proactive antisocial behavior increased from middle childhood to adolescence. Following the hypothesis that reactive, but not proactive aggression is associated with ADHD in adult offenders, we performed a study in adult offenders with and without ADHD, who had committed violent crimes.…”
Section: Introductionmentioning
confidence: 99%
“…Consider the function of aggression. Whereas ADHD is associated with both reactive and proactive aggression, albeit moreso with the former (Bennett et al 2004;Dodge et al 1997;Waschbusch et al 1998), anxiety has only been positively associated with reactive aggression (Raine et al 2006;Vitaro et al 2002). This is not surprising given that reactive aggressive behaviors are hasty reactions to perceived threat or hostility (Card and Little 2006), and both impulsivity and biased attributions are impaired in youth with ADHD as well as anxiety (e.g., Luebbe et al 2010;Wilens et al 2002).…”
Section: Aggressive Subtypesmentioning
confidence: 99%